Continuity Business of Coffe Shop in Malang City in the Facing of Covid-19 Pandemic - Bayu Ilham Pradana; Ema Zahra Firdaus; Rini Safitri (International Journal of Applied Business and International Management, 2023)
In the midst of the impact of the pandemic, coffee shops are facing problems in maintaining the continuity of their business. For this reason, it is important for coffee entrepreneurs shop to have an entrepreneurial and innovation orientation. This study aims to determine the effect of entrepreneurial orientation and innovation toward business continuity. This type of research is explanatory research using path analysis. The population of this research is coffee SMEs shop in Malang City who have started their business for at least two years. Respondent data comes from umkm.depkop.go.id with the keyword coffee shops and coffee shops, so that as many as 149 respondents were obtained. Based on the search, there are 132 coffee SMEs shops and coffee shops in Malang City that have been running the business for at least two years. The sample technique used is a saturated sample, so that all members of the population are sampled. Data was collected by distributing questionnaires. The results of this study are that there is an influence of entrepreneurial orientation on business continuity, there is an influence of entrepreneurial orientation on innovation, there is an influence of innovation on business continuity, and innovation has a mediating role in the influence of entrepreneurial orientation on the sustainability of coffee shops in Malang City.